Characterization of Acid Hydrolyzed Taro Boloso-I (Colocasia esculenta Cultivar) Starch as a Diluent in Direct Compression of Tablets - Solomon Gashaw; Afewerk Getachew; Fantahun Mola (Advances in Pharmacological and Pharmaceutical Sciences)
Corn, wheat, rice, potato, and cassava starches have been widely used as pharmaceutical excipients. However, the search for cost-effective local starch alternatives is necessary due to the availability and usage constraints. In Ethiopia, various plant species, including Taro Boloso-I, have been explored as potential sources of pharmaceutical starch. It is a variety of Colocasia esculenta with a high tuber yield and high starch content. However, the native starch requires modifications to enhance its functionality. Therefore, this study aimed to improve the native starch through acid modification and evaluate its performance as a direct compressible tablet excipient. The native starch was treated with a 6% w/v HCl solution for 192 hours, resulting in acid-modified Taro Boloso-I starch, which was then evaluated for suitability for direct compression. XRD patterns of both the native and modified starch showed characteristic A-type crystals, with significantly higher relative crystallinity observed in the latter. Additionally, the acid-modified starch exhibited a lower moisture content and improved flow properties. The compaction study also demonstrated its improved compactibility (tensile strength: 16.82 kg/cm2), surpassing both the native starch (13.17) and Starch 1500® (11.2). The modified starch also showed a lower lubricant sensitivity compared to the native starch and Starch 1500®. Furthermore, paracetamol tablets made with the modified starch exhibited higher mechanical strength and lower friability in all paracetamol concentrations. It incorporated up to 40% paracetamol while maintaining acceptable tablet characteristics, whereas the native starch and Starch 1500® were limited to 30% (w/w). Based on these findings, the modified starch showed promise as an alternative direct compressible excipient in tablet manufacturing.